No significant steady state surface creep along the North Anatolian Fault offshore Istanbul: Results of 6 months of seafloor acoustic ranging. Issue 13 (2nd July 2016) - Sakic, P.; Piété, H.; Ballu, V.; Royer, J.‐Y.; Kopp, H.; Lange, D.; Petersen, F.; Özeren, M. S.; Ergintav, S.; Geli, L.; Henry, P.; Deschamps, A.
Abstract: The submarine Istanbul‐Silivri fault segment, within 15 km of Istanbul, is the only portion of the North Anatolian Fault that has not ruptured in the last 250 years. We report first results of a seafloor acoustic ranging experiment to quantify current horizontal deformation along this segment and assess whether the segment is creeping aseismically or accumulating stress to be released in a future event. Ten transponders were installed to monitor length variations along 15 baselines. A joint least squares inversion for across‐fault baseline changes, accounting for sound speed drift at each transponder, precludes fault displacement rates larger than a few millimeters per year during the 6 month observation period. Forward modeling shows that the data better fit a locked state or a very moderate surface creep—less than 6 mm/yr compared to a far‐field slip rate of over 20 mm/yr—suggesting that the fault segment is currently accumulating stress. Key Points: A seafloor monitoring experiment was initiated to quantify deformation across the Istanbul‐Silivri segment of the North Anatolian Fault The first 6 months of data indicate no significant seafloor deformation across the fault Forward modeling suggests that the fault segment was partially or completely locked during the measurement period